Uso de instrumentos financieros derivados y rentabilidad de empresas no financieras de la Bolsa de Valores de Lima - Dominguez Soto, Leenin Krenlin (2022)
Objective: To establish the relation between the use of derivative financial instruments and the profitability of non-financial companies in Lima’s Stock Exchange (LSE). Method: The research was quantitative in nature with a non-experimental design and transversal of correlational type. By using information from 149 non-financial companies, the model of structural structures was applied in order to know the relation between the variables. Results: It is evident that the financial instruments derived from interest rate, exchange rate and price have a low positive relations with the profitability of the non-financial companies of the LSE. Conclusion: Although there is a positive relation between the use of derivative financial instruments and the profitability of non-financial companies on the LSE, it is not significant, which may be due to the small number of companies that used financial instruments.